Mengukur Persepsi Masyarakat Terhadap Pembangunan Flyover di Kota Bandar Lampung - Srei Nur Astuti; Novita Tresiana; Eko Budi Sulistio (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
The construction of flyover infrastructure in Bandar Lampung City is one of the government’s solutions to address traffic congestion problems, which also give rise to other issues. This infrastructure development not only generates objective impacts but also creates various public perceptions of the changes that occur. This study aims to measure and analyze public perceptions of flyover development in terms of psychological, environmental, economic, and social aspects. This research employs a quantitative approach with a descriptive method. The data analysis techniques used are descriptive statistics and categorization. The results show that public perceptions of flyover development vary across each aspect. In the psychological aspect, public perception tends to be positive, particularly in terms of comfort and safety. In the economic aspect, public perception is positive regarding the smoothness of economic activities. In the environmental aspect, public perception tends to be neutral to negative, especially related to noise and cleanliness. In the social aspect, public perception is positive regarding increased mobility. In conclusion, the construction of flyover infrastructure generates diverse perceptions among the community across several aspects.